Експериментальне дослідження теплоакумулюючих матеріалів на стенді - Клюєва, Олександра; Русанов, Сергій; Шатохіна, Ірина; Клюєв, Олег (ТзОВ «Галицька видавнича спілка», 2021)
We carried out experiments to determine the properties of a heat-accumulating material (ozokerite) on an experimental bench. We have obtained experimental data on the time of heating the liquid to the optimum and the movement speed of the working liquid.
Field research of heat-accumulating materials on the bench
Keywords: 66.067.1; 62172